Antibacterial and antioxidant activity of endophytic fungi extracts isolated from the petiole of sungkai plant (Peronema canescens) - RIAN OKTIANSYAH; ELFITA ELFITA; HARY WIDJAJANTI; SALNI SALNI; ARUM SETIAWAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Oktiansyah R, Elfita, Widjajanti H, Salni, Setiawan A. 2023. Antibacterial and antioxidant activity of endophytic fungi extracts isolated from the petiole of sungkai plant (Peronema canescens). Biodiversitas 24: 6516-6526. Indonesia has a diverse number of medicinal plants that are very helpful in preventing infectious diseases. Sungkai (Peronema canescens) is a medicinal plant of the family Verbenaceae that is often used and found in Indonesia. Its leaves possessed antibacterial and antioxidant properties that boost immunity and lessen the signs of infectious disorders. This study explored the types of endophytic fungi found in sungkai petioles and examined their relationship to previously reported sungkai leaf endophytic fungal isolates and spectrum of compounds contained them. Endophytic fungal were isolated from fresh leaf petioles of host plants, and their morphological and molecular characteristics were determined. Endophytic fungal extracts were tested for antibacterial and antioxidant properties. Utilizing the paper disk diffusion technique, the antibacterial characteristics were ascertained, while the DPPH method was used to determine antioxidant activity. Molecular identification was carried out on the fungal isolate with the most potential, and chemical compounds were isolated using column chromatography. The structures of the compounds were determined using spectroscopy, including 1D and 2D NMR. Eight endophytic fungal isolates were obtained from sungkai leaf stalks (RA1-RA8) of various species of the genus Trichoderma. Differences in the diversity of endophytic fungi found in leaf stalks and endophytic fungi from leaves were identified. RA1 showed the strongest antibacterial and antioxidant activity and was molecularly identified as T. harzianum. Spectroscopic analysis showed that the pure compound contained within was 9-hydroxy-7-methylenebenzo[c]oxepin-3(7H)-one (1), which had never previously been found in sungkai plants and endophytic fungi. The antibacterial activity of Compound 1 is in the strong category (MIC = 64 µg/mL) but is not active as an antioxidant. In terms of producing medicinal ingredients from endophytic fungi, T. harzianum in extract form has more potential to be developed.